Using natural means to reduce surface transport noise during propagation outdoors. (May 2015) - Van Renterghem, Timothy; Forssén, Jens; Attenborough, Keith; Jean, Philippe; Defrance, Jérôme; Hornikx, Maarten; Kang, Jian
Abstract: This paper reviews ways of reducing surface transport noise by natural means. The noise abatement solutions of interest can be easily (visually) incorporated in the landscape or help with greening the (sub)urban environment. They include vegetated surfaces (applied to faces or tops of noise walls and on buildings' façades and roofs), caged piles of stones (gabions), vegetation belts (tree belts, shrub zones and hedges), earth berms and various ways of exploiting ground-surface-related effects. The ideas presented in this overview have been tested in the laboratory and/or numerically evaluated in order to assess or enhance the noise abatement they could provide. Some in-situ experiments are discussed as well. When well designed, such natural devices have the potential to abate surface transport noise, possibly by complementing and sometimes improving common (non-natural) noise reducing devices or measures. Their applicability strongly depends on the available space reserved for the noise abatement and the receiver position.